2021
DOI: 10.1172/jci.insight.147464
|View full text |Cite
|
Sign up to set email alerts
|

Urinary EGF and MCP-1 and risk of CKD after cardiac surgery

Abstract: and is co-inventor "Biomarkers and methods for progression prediction for chronic kidney disease"patent. All other authors declare that no conflicts of interest exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…The CCL2 gene that encodes MCP-1 is expressed primarily in the ascending loop of Henle and distal tubule 41 . Higher levels of both plasma and urinary MCP-1 were shown to be important biomarkers of AKI 42 , 43 , and we have previously shown that gene expression of CCL2 and urinary MCP-1 levels are elevated in the setting of cardiac surgery-associated AKI 44 . Higher urinary MCP-1 levels also associated with chronic tubule-interstitial damage and CKD progression in various settings such as IgA nephropathy, diabetes mellitus, and obstructive uropathy 41 , 45 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 79%
“…The CCL2 gene that encodes MCP-1 is expressed primarily in the ascending loop of Henle and distal tubule 41 . Higher levels of both plasma and urinary MCP-1 were shown to be important biomarkers of AKI 42 , 43 , and we have previously shown that gene expression of CCL2 and urinary MCP-1 levels are elevated in the setting of cardiac surgery-associated AKI 44 . Higher urinary MCP-1 levels also associated with chronic tubule-interstitial damage and CKD progression in various settings such as IgA nephropathy, diabetes mellitus, and obstructive uropathy 41 , 45 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 79%
“…The progression to CKD after CTS-AKI represents another area where biomarkers may add additional prognostic information. In the TRIBE-AKI cohort, epidermal growth factor (EGF) and monocyte chemoattractant protein-1 (MCP-1) were strongly associated with the risk of progression to CKD [103].…”
Section: Discussionmentioning
confidence: 99%
“…The data analysis had no covariates with missing data. In addition, five imputed datasets with chained equations were created using R-package mice ( 16 ). Our multiple imputation of the dataset was mainly based on the following principles: (1) there were no missing data for the primary outcome; (2) replacement of categorical variables was not advisable, as the plausibility is still debated; (3) 5% missingness is suggested as a maximum upper threshold below which multiple imputation provides benefit.…”
Section: Methodsmentioning
confidence: 99%